2011
DOI: 10.1590/s0103-51502011000100019
|View full text |Cite
|
Sign up to set email alerts
|

Comparação dos exercícios em cadeia cinética aberta e cadeia cinética fechada na reabilitação da disfunção femoropatelar

Abstract: ResumoIntrodução: A disfunção femoropatelar (DFP) é uma patologia caracterizada por dor na região patelofemoral resultante de alterações físicas e biomecânicas dessa articulação. Seu índice de incidência é alto, representando uma queixa comum em cerca de 20% da população, e sua etiologia ainda permanece desconhecida. Objetivo: Esta revisão de literatura tem como objetivo comparar a eficácia dos exercícios em cadeia cinética aberta com os em cadeia cinética fechada, para a recuperação funcional dos portadores d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…The quadriceps muscle is responsible for activating the forces exerted on the patella, whose function is to control the position of the patella in relation to the trochlea (9). Improper positioning of the patella, differences in quadriceps muscle recruitment and pain can affect balance and motor control in PFPS (10).…”
Section: Introductionmentioning
confidence: 99%
“…The quadriceps muscle is responsible for activating the forces exerted on the patella, whose function is to control the position of the patella in relation to the trochlea (9). Improper positioning of the patella, differences in quadriceps muscle recruitment and pain can affect balance and motor control in PFPS (10).…”
Section: Introductionmentioning
confidence: 99%
“…Palletofemoral pain syndrome (PFPS), characterized by anterior knee pain with no definitive cause or diagnosis (1), can be defined as pain around the kneecap (patella) resulting from physical and biomechanical changes in this joint (2). Other commonly used terms include anterior knee pain, chondromalacia patella, palletofemoral arthralgia and palletofemoral pain (3).…”
Section: Introductionmentioning
confidence: 99%
“…Although some authors suggest that CKC, such as squat, can be safer for patients with PFPS, since they provide dynamic stabilization of the joint, causing a closer relation between the activations levels of VM and VL, 20,30 and that studies like Fehr et al 31 consider that CKC is more efficient for improving functionality when compared to OKC exercises, Escamilla 32 emphasizes that the squat is a functional activity which bears complaints among the patients with PFPS, and Escamilla et al 33 concluded that the OKC produce lower compressive forces when compared to CKC, which generates bigger compressive forces, especially in angles above 85°.…”
mentioning
confidence: 99%